Omega-3 Supplementation Lowers Inflammation in Healthy Middle-Aged and Older Adults: A Randomized Controlled Trial - Kiecolt-Glaser, Janice K. (2012)
Observational studies have linked lower levels of omega-3 (n-3) polyunsaturated fatty acids (PUFAs) with inflammation and depression. This study was designed to determine whether n-3 supplementation would decrease serum cytokine production and depressive symptoms in 138 healthy middle-aged and older adults (average age=51.04, SD=7.76) who were sedentary and overweight (average BMI=30.59, SD= 4.50). This three-arm randomized, placebo-controlled, double-blind 4-month trial compared responses to (1) 2.5 g/d n-3 PUFAs, or (2) 1.25 g/d n-3 PUFAs, or (3) placebo capsules that mirrored the proportions of fatty acids in the typical American diet. Serum interleukin-6 decreased by 10% and 12% in our low and high dose n-3 groups, respectively, compared to a 36% increase in the placebo group. Similarly, low and high dose n-3 groups showed modest 0.2% and −2.3% changes in serum tumor necrosis factor alpha, compared to a 12% increase in the control group. Depressive symptoms were quite low at baseline and did not change significantly in response to supplementation. Our data suggest that n-3 PUFAs can reduce inflammation in overweight, sedentary middle-aged and older adults, and thus could have broad health benefits. These data provide a window into the ways in which the n-3 PUFAs may impact disease initiation, progression, and resolution. ClinicalTrials.gov identifier: NCT00385723